Relationship of Power, Waist Muscle Flexibility, and Power Muscle Legs Against Smash Volleyball For FIK UNM Makassar Students - Hikmad Hakim; Anto Sukamto; Rahma Dewi; Nurkadri (UNIB Press, 2022)
Power Leg Muscle Power volleyball for FIK UNM Makassar students. The sample used in this study were FIK UNM Makassar students who took volleyball courses. Data analysis techniques used to test the hypothesis are normality test, linearity test, and correlation test. From the results of the first hypothesis correlation test, a significance value of 0.046 < 0.05 was obtained, so there was a significant relationship between power arm muscle smash. The results of the second hypothesis test have a significance value of 0.037 < 0.05, so there is a significant relationship between Waist Muscle Flexibility and Smash. The results of the third hypothesis test have a significance value of 0.032 < 0.05, so there is a significant relationship between Waist Muscle Flexibility and Smash. Based on the multiple correlation test in the summary model table, it is known that the magnitude of the relationship between arm muscle power, waist muscle flexibility and leg muscle power (simultaneously) on the smash results calculated by the correlation coefficient is 0.452, this indicates a moderate effect. Meanwhile, the simultaneous contribution or contribution of the arm muscle power variable with the flexibility of the waist muscles is 20.4% while 79.1% is determined by other variables.